2002
DOI: 10.1016/s1525-1578(10)60699-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Loss of Heterozygosity Analysis by Using Single or Very Few Cells

Abstract: Loss of heterozygosity (LOH) is an indication of tumor suppressor gene inactivation. However, loss of heterozygosity analysis has been limited to either a small scale or to very few genetic markers. To significantly increase the scale of study and to include a large number of markers in the analysis, experimental conditions were established for using single cells or single cell equivalent with 10 markers typed simultaneously. Under these conditions, the allele amplification failure rate was 3.7% when single ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Our group has already developed a highly efficient multiplex PCR protocol that can be used to amplify a large number of loci that could be resolved either by conventional PAGE or by denaturing gradient gel electrophoresis (Lin et al 1996;Cui and Li 1998;Cui et al 2000). Very recently, we showed that 10 independent sequences may be amplified simultaneously from single diploid cells (Cui et al 2002). In the present study, we used a subgrouping strategy in the second round of amplification and successfully amplified 32 marker sequences from single sperm, compared with 5 or 6 in most studies with large amounts of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has already developed a highly efficient multiplex PCR protocol that can be used to amplify a large number of loci that could be resolved either by conventional PAGE or by denaturing gradient gel electrophoresis (Lin et al 1996;Cui and Li 1998;Cui et al 2000). Very recently, we showed that 10 independent sequences may be amplified simultaneously from single diploid cells (Cui et al 2002). In the present study, we used a subgrouping strategy in the second round of amplification and successfully amplified 32 marker sequences from single sperm, compared with 5 or 6 in most studies with large amounts of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, low amounts and often poor quality of DNA isolated from such material represent a serious obstacle to large-scale mutational studies. 4,5 Human tumors contain a high proportion of C to T transition mutations. 6 Human uracil-DNA glycosylase (UNG) is a major DNA glycosylase that counteracts accumulation of such mutations in the genome.…”
Section: (J Mol Diagn 2005 7:36 -39)mentioning
confidence: 99%
“…PCR primers are designed based on the selected sequences, so that amplification with these primers generates PCR products of different lengths and can be resolved by regular gel electrophoresis. Experimentally, the marker sequences are amplified with a two‐round multiplex protocol developed in our laboratory (112–114). If the number of marker sequences is large, the sequences may be amplified separately in different groups in the second round to ensure the resulting fragments are easily resolved.…”
Section: New Tools For Understanding Gene Segment Organization In Thementioning
confidence: 99%